2012
DOI: 10.1016/j.ijheatfluidflow.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of high-conductivity materials in film cooled turbine nozzles

Abstract: This study presents an experimental and numerical investigation of the beneficial effect of higher conductivity materials in HP turbine nozzles. Most of the literature studies focus on the maximum temperature that a nozzle can withstand, whereas the effect of thermal gradients is often neglected. However thermal gradients have higher influence on the life of the components and they have to be given careful consideration. In this work it is shown that thermal gradients are reduced by using high conductivity mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 26 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…The main goal is increasing heat transfer while reducing thermal gradients across the blades and minimize the energy used for coolant purpose (Saha and Acharja 2014). Temperature uniformity is strongly required to avoid cracks and ensure high level of reliability; this aspect is still considered one of the greatest challenges in gas turbine production (Bunker 2007;Montomoli et al 2012). In order to predict the metal temperature accurately, it is important to carry out a conjugate heat transfer (CHT) method, where the thermal field in the fluid and the solid are solved at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal is increasing heat transfer while reducing thermal gradients across the blades and minimize the energy used for coolant purpose (Saha and Acharja 2014). Temperature uniformity is strongly required to avoid cracks and ensure high level of reliability; this aspect is still considered one of the greatest challenges in gas turbine production (Bunker 2007;Montomoli et al 2012). In order to predict the metal temperature accurately, it is important to carry out a conjugate heat transfer (CHT) method, where the thermal field in the fluid and the solid are solved at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Lee investigated on a key vortical structure in film cooling flow, which is called counter-rotating vortex pair (CRVP) in order to increase the effectiveness during film cooling on turbine blades. Montomoli (2012) conducted numerical as well as experimental investigation to study the effect of higher conductivity materials in HP turbine nozzles. They concluded that using nickelaluminide alloys in nozzles reduce the thermal gradients from 3 to 4 times.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it is a large challenge for the design of turbine devices, especially NGV, owing to the non-uniform temperature profiles of turbine inlet (combustor outlet). To investigate the interacting influences between total pressure and temperature radial gradients on heat transfer performance of a high-pressure turbine vane, Barringer et al [5,6] developed a combustor simulator and revealed pressure gradient seriously influencing vane heat transfer [7]; Povey et al [8] also simulated the engine combustor exit realistic temperature profiles. The subsequent studies revealed the influences of hot spot on the heat transfer of both NGV and intermediate pressure vanes [9].…”
Section: Introductionmentioning
confidence: 99%